The importance of data acquisition, analysis and integration from E-Business and Supply Chain Management using Management Information System (MIS) of ShopUp - D Costa, Anthony Simon (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2021.